IDENTIFIKASI KEMAMPUAN SISWA DALAM PEMECAHAN MASALAH MISKONSEPSI PADA MATERI FLUIDA DINAMIS DI TINGKAT SMA - Ramadhani, Nabila; Manullang, Sampang Rotua; Br. Simbolon, Valentina Agustus (EduFisika: Jurnal Pendidikan Fisika, 2022)
One of the main problems that arise in physics education is students' One of the main problems that often arise in physics education is students' misconceptions, especially on Dynamic Fluids. The purpose of this study was to find out students who experienced misconceptions, did not understand the concept, understood the concept and partially understood the dynamic fluid material. The data analysis technique in this study is quantitative and qualitative data analysis by collecting data on concept understanding test sheets and in-depth interview guidelines with informants/research subjects. The subjects of this study were students of class XI MIA from several schools consisting of 34 students. Based on data analysis, 62.38% of students still experience misconceptions about dynamic fluid material. And 16.48% of students do not understand the concept. Then 21.18% of students have understood the concepts previously presented by researchers with scientific reasons that can be proven true. With that it can be concluded that there are still many students who have misconceptions about dynamic fluid material. Keywords: Misconceptions, Dynamic Fluids.